Comparison of patient satisfaction with mini-implant versus standard diameter implant overdentures: a systematic review and meta-analysis of randomized controlled trials - Gowri Sivaramakrishnan; Kannan Sridharan (SpringerOpen, 2017)
Abstract Mini-implants have certain advantages over standard size implants which are being tested in various randomized controlled trials. This systematic review and meta-analysis aims to compare conventional implant overdentures to mini-implant-retained overdentures as regards to patient satisfaction. Electronic databases were searched for eligible studies data required were extracted. The extracted data were analyzed using non-Cochrane mode in RevMan 5.0 software. The heterogeneity between the studies was assessed using Forest plot, I 2 statistics, and chi-square test with a statistical P value of less than 0.10 to indicate statistical significance. Random-effect models were used in case of moderate heterogeneity. Four studies were included for the review and two for meta-analysis. Two studies in 177 patients comparing quality of life with mini or standard diameter implants showed a pooled result of −4.76 [−6.48, −3.04] favoring the use of mini-implants. The results for other outcomes were incomputable due to inadequate studies. GRADE approach was used for quality of life, and the strength of evidence was observed to be "low". Mini-implant-supported overdentures had better patient satisfaction levels compared to standard diameter implant overdenture. There is definite lack of evidence to support the use of mini-implants for overdentures.